Mastering card sorting : how to use research to organize information intuitively (O'Reilly Media, 2018)
"Keeping a website or app's navigation and information architecture organized is critical to its usability. Users get frustrated when they can't find what they're looking for and a confusing navigation can hide content that you want them to discover. Fortunately, card sorting is an easy-to-learn research method that can guide you in creating intuitive navigation and information architecture. In this intermediate-level video, UX pro Elizabeth Allen shows you how to plan and conduct a card sort, and then teaches you some simple methods for analyzing both quantitative and qualitative card sort data. By the end of this video, you'll possess the tools you need to get your website or app organized in a way that aligns with user expectations and behaviors."--Resource description page